(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Across the globe, the lives of individuals suffering from rare diseases are seen to profoundly impact their physical, emotional, social, and financial situations. It is therefore crucial to provide support networks and advocate for improved medical care and resources to improve their quality of life. Well before such attempts, it is quite important to check the level of awareness among people about rare diseases and their symptoms. The present study aims to assess the level of awareness among the non-medical young population of Gujarat state regarding rare diseases and the associated challenges. Through the use of a mixed-methods approach including binary, descriptive, and multiple-choice questions, the researchers gathered data from a diverse sample of respondents. The findings revealed a mixture of responses highlighting the complexity and nuances surrounding the understanding and awareness of rare diseases in the youth of Gujarat.